Object-Oriented Analysis, Design and Implementation - Dathan, Brahma; Ramnath, Sarnath (Springer, 2015)
The second edition of the book includes revisions based on the feedback received from a number of sources on the first edition. The case-study-based approach to the principles of object-oriented design has been mostly well-received. There were two suggestions that we felt needed action on our part: 1. A complete reference for UML. The first edition was built on the pedagogical philosophy that the tools of the trade would be presented on an as-needed basis. Accordingly, UML diagrams were introduced in the context of case studies, and we avoided discussing the UML diagrams that were not needed. Some readers felt that the book was incomplete without connecting the content to the remainder of UML. 2. The need for a conclusion. Although each chapter ended with a conclusion that connected the material with previous chapters, some readers and critics felt that a concluding chapter would be useful. Chapter 13 in the new edition addresses both these issues. In this chapter we have attempted to provide a concise introduction to the remainder of UML diagrams. In keeping with our philosophy, we have avoided presenting simply the technicalities of the diagrams with disjointed examples and gone with a holistic approach. We have used the OMG classification of the UML diagrams as the six views of object-oriented system, and explained the role played by each view. We have then discussed the diagrams that represent each view and connected these views to the case studies presented in the book. We hope that this chapter will both provide the user with a concise introduction to all of UML and also round off the text by connecting all aspects of object-oriented design.
An Integrated Approach